Fauna of click beetles (Coleoptera: Elateridae) in the interfluve of Rivers Moksha and Sura, Republic of Mordovia, Russia - ALEXANDER B. RUCHIN; LEONID V. EGOROV; GENNADY B. SEMISHIN (Biodiversitas Journal of Biological Diversity, 2018)
Ruchin AB, Egorov LV, Semishin GB. 2018. Fauna of click beetles (Coleoptera: Elateridae) in the interfluve of Rivers Moksha and Sura, Republic of Mordovia, Russia. Biodiversitas 19: 1352-1365. The results of the study of fauna of click beetles in the Republic of Mordovia are presented. By now, 58 species of click beetles have been recorded here. Adrastus pallens is a new record for the republic. As per the literature information, 6 species of click beetles (Agriotes pilosellus, Melanotus crassicollis, Melanotus fusciceps, Liotrichus affinis, Pseudanostirus globicollis, Stenagostus rufus) are known and these indications require confirmation. Two species (Agriotes acuminatus, Limoniscus suturalis) are excluded from the fauna. Taking into account the literary information in the fauna of Mordovia, 64 species of Elateridae are known. Agrypnus murinus, Agriotes lineatus, Agriotes obscurus, Agriotes sputator, Dalopius marginatus, Ampedus balteatus, Ampedus pomorum, Hemicrepidius niger, Athous subfuscus, Prosternon tessellatum, Selatosomus aeneus are among the mass species. A list of the species is presented, which with a high degree of probability can still be found in the republic.